The Effectiveness of Google Classroom as Asynchronous Learning Media in Civics Learning - Setiawati, Tusti; Prakarsa, Ega (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2021)
Learning through asynchronous google classroom media is considered a learning solution during a pandemic. Unlike learning through synchronous media, the limitations of accessing technological devices such as laptops and smartphones can be overcome in asynchronous learning in google classroom. The purpose of this study is to see the effectiveness of google classroom as an asynchronous medium that is still used by teachers in Civics learning.This study uses a quantitative approach.Descriptive statistics are used to measure the distribution of respondents' responses to the research questionnaire. The questionnaire was distributed within a span of 7 days via google form and 30 teachers were selected as respondents in this study. The results of this study indicate that google classroom as an asynchronous media tends to be used by teachers and is considered effective in learning Citizenship Education (Civics). This research has implications as a scientific reference so as to encourage the extensification of e-learning learning theory, and can be used as material for evaluation and formulation of policies in the scope of learning.